Rapid and sensitive detection of pesticide residues using dynamic surface‐enhanced Raman spectroscopy. (19th January 2020) - Chen, Wanling; Long, Feng; Song, Guofen; Chen, Jing; Peng, Shuai; Li, Penghui
Abstract: Pesticide residues are one of the major food safety concerns for consumers all over the world, and it is crucial to develop simple, rapid, and effective method for the detection of pesticide residues. In the study, we report the sensitive detection of pesticides with the dynamic surface‐enhanced Raman spectroscopy (dynamic SERS) method. The dynamic SERS method provides excellent detection sensitivity at the metastable state of plasmonic nanoparticles in the sessile drop, which is a critical state between the wet state and dry state during the volatilization process. With this simple and rapid method, the SERS performance towards four pesticides, paraquat, thiabendazole, tricyclazole, and isocarbophos, is investigated with silver nanoparticles (AgNPs) as the enhancing reagents. The characteristic SERS spectra of paraquat, thiabendazole, tricyclazole, and isocarbophos can be detected at concentrations down to 1 × 10 −9 M, 5 × 10 −9 M, 5.28 × 10 −9 M, and 3.45 × 10 −7 M, respectively. The pesticides are also discriminable at the same concentrations as the standard solution counterparts from the pesticides spiked vegetable extracts, and linear relationship can be drawn from the characteristic peak intensities and negative logarithm of concentrations of the four pesticides. Therefore, the simple and rapid dynamic SERS method shows great potential in the practical detection of pesticide residues. Abstract : Sensitive detection of paraquat, thiabendazole, tricyclazole, and isocarbophos in vegetable extracts is achieved with the dynamic surface‐enhanced Raman spectroscopy method.